Cooperative financial institutions (CFIs) as a source of development finance - a case study on Sub-Saharan Africa - Nzila, Michelo M (Research of GSB, 2018)
The lack of access to finance is cited as one of the major barriers preventing developing countries from attaining economic development. While traditional sources of financing such as Official Development Assistance (ODA), Foreign Direct Investment (FDI) and Remittances have done much to alleviate the problem, they have left what is termed the missing middle; a financing gap created by failure to provide financing particularly for Micro, Small and Medium Enterprises (MSMEs) and for the poor in the subject countries. The major impediments have included lack of collateral, inadequate training and business knowledge and risk aversion on the part of traditional financial institutions such as banks. Further, domestic resource mobilization endeavours have concentrated on tax reforms to improve governments' revenue collection and administration, leaving personal savings aggregation unattended. This financing gap is despite knowledge that MSMEs possess the most potential for employment creation, thus poverty alleviation for the masses. Cooperative Financial Institutions have been in existence for a long time and have the potential to provide innovative solutions in addressing the problem at hand. They have however, received little attention and recognition and the historical association with agriculture and the older generation has limited their outreach and impact. This study is thus intended to explore whether CFIs can bridge the financing gap for MSMEs in Sub-Saharan Africa.